Colonic volvulus detected by CT scan in a case with mental retardation and prune belly syndrome - Yoichiro Oka; Kouji Masumoto; Masatoshi Nakamura; Akinori Iwasaki (Asian Journal of Surgery, 2011)
Colonic volvulus is a rare disease in children. Delayed diagnosis of the condition can often be fatal, especially in pediatric patients with mental retardation. We herein present the case of a female pediatric patient with colonic volvulus, prune belly syndrome, and mental retardation. Preoperative CT scans showed the characteristic signs of this disease. The volvulus occurred in the proximal colon of the colostomy. The release of the colonic volvulus and reconstruction of the colostomy were performed without the resection of the ischemic colon. The postoperative clinical course was uneventful.